Yasynskyy V.K., Yurchenko I.V. Mean-Square Stability and Instability Criteria for the Gikhman–Ito Stochastic Diffusion Functional Differential Systems Subject to External Disturbances of the Type of Random Variables // Cybernetics and Systems Analysis.– 2023.– Vol.59, N2.– P.283–295. - Yurchenko, Igor Valeryjovych; Yasynskyy, Volodymyr Kyryllovych (Springer Nature, 2023)
Mean-Square Stability and Instability Criteria for the Gikhman–Ito Stochastic Diffusion Functional Differential Systems Subject to External Disturbances of the Type of Random Variables.
Keywords: Mean-Square Stability; Stochastic Diffusion Functional Differential Systems; External Disturbances